Entre o Projecto Analógico e o Digital: Continuidade e Rutura - Márcio André Brito Rodrigues (2014)
T his study discusses the analogical/ digital instrumental dialectics and the semiotic role of the computer in the architectural project. For such an analysis we present a theoretical framework that explores the definition of technology in Heidegger and Bragança de Miranda (and the variant technoideology proposed by Fernando Lisboa). We complement this analysis with the notions of alienation and fantasy described by Neil Leach and José Gil followed by a look into the relationship between mankind and its working tools, evoking some ideas of Marshall McLuhan, who defined the contemporary hermeneutic of media and information. We present the notion of augmented intelect, explored by Licklider and Engelbart. To complete the introduction we expose a summarized study about the use of the computer in the architectural design, in the past 50 years, framing it in an analogical or digital usage which, in that sense, goes from Sutherland´s sketchpad to the latest construction achievments made possible by new technologies. In the second part, we present three case studies in order to clarify the concepts introduced in the theoretical framework. The focus is on the analysis of works that allow us to discuss working methodologies and, in particular, the media used. Thus, we prioritize the examples where there are connections, however subtle, between a more analogical approach and a more digital one. Frank Gehry's work will be examined with a particular focus on the digitizing of the Guggenheim Museum in Bilbao. We present the investigation work conducted by the architect José Pinto Duarte, particularly in his doctoral thesis which will be an introduction to the concept of axiomatization of architectural design, according with William Mitchell and the semiotic structures of the american protopragmatism; the Sagrada Família Basilica, with particular emphasis on the work coordinated by the architect Mark Burry and finally, we present a project carried out at the atelier Mecanoo Architecten. In the last , the connections between the aforementioned examples and the conceptual and theroretical framework, as well as their contribution to the goal of this study, will be pointed up.